Analysis of the cooked aroma and odorants that contribute to umami aftertaste of soy miso (Japanese soybean paste). (15th December 2016) - Inoue, Yutaka; Kato, Sachie; Saikusa, Miyu; Suzuki, Chihiro; Otsubo, Yuriko; Tanaka, Yutaro; Watanabe, Hirohito; Hayase, Fumitaka
Highlights: Soy miso is used for imparting umami aftertaste to cooked dishes. Large differences have been found between cooked aroma of rice miso and soy miso. Dimethyl trisulfide, one of the odorants of soy miso, contributes to the taste. Our findings will contribute to the control of the umami profile in miso-based food. Abstract: Soy miso, the traditional Japanese fermented soybean paste prepared using soybean koji, is used for imparting umami aftertaste to cooked dishes. The objective of this study was to identify the key odorants of cooked soy miso and their influence on umami aftertaste perception. Volatile compounds of soy miso and two rice misos were prepared using simultaneous distillation-extraction, and the key odorants were identified by using the gas chromatography-olfactometry/aroma extract dilution assay approach, and soy miso was compared with rice misos. Forty-one aroma-active compounds were detected in cooked soy miso, and malty, green, roasty and sulfury aromas were identified as the characteristic aromas. Finally, sensory evaluation was conducted to assess the contribution to the umami aftertaste of six key compounds with the highest flavour dilution factor. Results revealed that dimethyl trisulfide, which was newly identified in cooked miso, contributes to the umami aftertaste and palatability of cooked soy miso.